HUBUNGAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK ETIKET SISWA SMK BROADCASTING BINA CREATIVE (BBC) MEDAN DI ERA DIGITAL (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted under the supervision of Bangun Munte, S.Pd., M.M and Hersakso Sinurat, M.Div., M.Si.Teol at the Faculty of Teacher Training and Education, HKBP Nommensen University Medan. the relationship of christian religious education teache rs in forming etiquette of students at bina creative (bbc) medan broadcasting vocational school in the digital era digital. The background of this research arises from the observable decline in students’ ethics as a result of the rapid advancement of digital technology and the widespread use of social media. This research applies a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The variables examined in this study include the role of Christian Religious Education teachers as the independent variable (X) and students’ ethics as the dependent variable (Y). The findings reveal that the role of Christian Religious Education teachers falls into a positive category and shows a meaningful contribution in shaping students’ ethics. Teachers function as transmitters of values, as well as moral and spiritual mentors, and character developers who are capable of enhancing students’ attitudes, discipline, responsibility, and communication ethics, both in direct interactions and within digital contexts. In conclusion, the role of Christian Religious Education teachers is proven to be effective in improving students’ ethical behavior in the digital era, and it plays an important part in strengthening students’ character grounded in Christian values.